Independent risk factors associated with infant deaths - Anna Lúcia da Silva; Thais Aidar de Freitas Mathias (Escola Paulista de Enfermagem, Universidade Federal de São Paulo, 2014)
OBJECTIVE: Identifying the independent risk factors associated with infant deaths registered in Brazilian public information systems.METHODS: A cross-sectional study using secondary data recorded in public information systems for eleven years. The association of mortality rates was observed according to death periods using univariate and multivariate regression tests.RESULTS: The infant mortality rate decreased by 20.7 % in the study period. The list of independent factors associated with infant deaths shows the necessity for measures to increase public actions aimed at the early onset of prenatal care, continuing until the postpartum, puerperal period and in the growth and development of the newborn.CONCLUSION: The independent risk factors for infant death were low birth weight, gestation duration of less than 37 weeks, multiple pregnancy, maternal educational level lower than eight years, Apgar score and less than seven antenatal pregnancy.